One-step preparation of UV transparent highly ordered mesoporous zirconia thin films - Zelcer, Andrés (2013)
Highly ordered mesoporous ZrO2 thin films were prepared by evaporation induced self-assembly. Complexing agents and low pH were simultaneously employed in order to control the hydrolysis-condensation kinetics, permitting to cast films in one step. Many commercially available PPO-based surfactants can be used as templates, yielding different pore sizes. The mesoporosity is well preserved at high temperatures (600 °C) and after exposing the films to extreme alkaline conditions (1 M NaOH, 18 h). The procedure has been used to cast multilayer films, paving the way to mesoporous thin films-based UV photonics. © The Royal Society of Chemistry 2013.